GAMBARAN KARAKTERISTIK DAN KECEMASAN IBU HAMIL TRIMESTER I TERHADAP PEMERIKSAAN TRIPLE ELIMINASI - Putri Maretyara Saptyani; Resti Ikhda Syamsiah; Laeli Farkhah Farkhah (IKesT Muhammadiyah Palembang, 2024)
Introduction: Triple Elimination is a health program based on the legal foundation of the Minister of Health Regulation number 52 of 2017 concerning the